Enhanced Stability of Li Metal Anodes by Synergetic Control of Nucleation and the Solid Electrolyte Interphase. Issue 42 (30th September 2019) - Peng, Zhe; Song, Junhua; Huai, Liyuan; Jia, Haiping; Xiao, Biwei; Zou, Lianfeng; Zhu, Guomin; Martinez, Abraham; Roy, Swadipta; Murugesan, Vijayakumar; Lee, Hongkyung; Ren, Xiaodi; et al.
Abstract: Use of a protective coating on a lithium metal anode (LMA) is an effective approach to enhance its coulombic efficiency and cycling stability. Here, a facile approach to produce uniform silver nanoparticle‐decorated LMA for high‐performance Li metal batteries (LMBs) is reported. This effective treatment can lead to well‐controlled nucleation and the formation of a stable solid electrolyte interphase (SEI). Ag nanoparticles embedded in the surface of Li anodes induce uniform Li plating/stripping morphologies with reduced overpotential. More importantly, cross‐linked lithium fluoride‐rich interphase formed during Ag + reduction enables a highly stable SEI layer. Based on the Ag‐LiF decorated anodes, LMBs with LiNi1/3 Mn1/3 Co1/3 O2 cathode (≈1.8 mAh cm −2 ) can retain >80% capacity over 500 cycles. The similar approach can also be used to treat sodium metal anodes. Excellent stability (80% capacity retention in 10 000 cycles) is obtained for a Na||Na3 V2 (PO4 )3 full cell using a Na‐Ag‐NaF/Na anode cycled in carbonate electrolyte. These results clearly indicate that synergetic control of the nucleation and SEI is an efficient approach to stabilize rechargeable metal batteries. Abstract : A thin, uniform silver‐lithium fluoride interlayer can be obtained on a Li metal anode by a facile ion‐exchange process, leading to well‐controlled nucleation and stable solid electrolyte interphase. Highly stable Li metal anodes obtained via this process can significantly improve the cycling stability of lithium metal batteries.